“Over the naked skin, the vale of ice” – drawing boundaries in The Pit by Ivan Goran Kovačić - Drenjančević, Ivana (Poznańskie Studia Slawistyczne, 2025)
This article takes an analytical look at the narrative poem The Pit (1944) by Ivan Goran Kovačić. In Kovačić’s work, the question of borders is important on many levels: The Pit belongs to the genre of the narrative poem, a genre on the border between the lyric and epic; it is written in sesta rima, a form in which rhyme emphasises the boundaries between verses; critics have also noted a partition between the first nine cantos and the tenth canto, as well as a distinct opposition between the executioner and the victims, the boundary between the individual statement of the narrator and the suffering collective. The analysis attempts to show that the narrator is more concerned with drawing the boundary between himself and the other victims than with the contradiction between himself and the executioner. It seems important to him to distinguish himself from them, which leads me to the conclusion that the narrator draws boundaries in order to escape the brutal collectivisation of death.